WEB SOFTWARE DESIGN, COMMUNICATION SYSTEMS, NAVIGATION AND INTEGRATION ALGORITHMS FOR SORTING ROBOTS - Nadhim Chafidz, Achmad
During the COVID-19 pandemic, the global e-commerce sector has experienced rapid growth. The major shift towards online shopping has brought new challenges in logistics, especially the increasing demand for goods delivery and distribution services by logistics companies. This situation creates several problems in the process of sorting and processing packages in the warehouses operated by these companies. Based on the results of visits and interviews at a small logistics warehouse in Bandung by the Electrical Engineering Final Project TA002 group, the warehouse is able to manually manage around 3,000 to 8,000 packages per day. Due to the heavy workload, workers often have to work overtime, causing human error in the sorting process. This manual sorting inaccuracy causes the packet processing process to be slower. In addition, sorting errors also cause additional workload on employees because they have to find packages that have been placed incorrectly and return them to the correct baskets or sacks. To overcome this problem, the TA002 Electrical Engineering Final Project group offers a solution in the form of a mobile robot-based logistics package sorting system. In this system, the sorting process starts with the mobile robot taking the packages from the workers. The worker then scans the QR code on the package using a smartphone, so that information about the destination city and basket for the package is received by the system and the mobile robot is ready for action. Next, the worker places the package on the mobile robot, which will deliver the package through a line-following method until it reaches the appropriate basket. The mobile robot will pour packets into the basket, then return to pick up the next packet from the worker to repeat the sorting cycle. If you use more than one mobile robot, each robot will work and coordinate with the others without colliding. By adopting this mobile robot-based sorting system, it is hoped that it can overcome the problem of human error and increase efficiency in the process of sorting and processing packages in the logistics warehouse. This Final Project book discusses the design and implementation of web apps, and robot algorithms. The two sections cover the user interface system, back end, scanner system, communication system, robot navigation algorithm, and robot integration algorithm. In general, it is discussed the development of web apps and scanners so that the labels of the packages to be sorted can be identified for the purpose of sorting after that the robot can walk to the right basket and put the package into the basket, after which the robot returns to the